Total Hyphema with Light Perception Vision Managed by Anterior Chamber Washout: A Case Report - Rofwiun; Nurul Elyana (International Medical Journal Corp. Ltd, 2026)
Introduction Ocular trauma represents a major etiology of monocular blindness and visual morbidity, frequently requiring emergent ophthalmological evaluation to prevent permanent deficits.1 Traumatic hyphema, defined as the presence of blood within the anterior chamber, typically arises from blunt or penetrating force that disrupts the vascular integrity of the iris or ciliary body.3 While most hyphemas are self-limiting, high-grade presentations (Grade III and IV) pose a significant risk for secondary complications such as ocular hypertension, secondary glaucoma, and corneal blood staining.5 The management of these cases is particularly complex in the immediate postoperative period following intraocular surgery, where the structural stability of the eye is already compromised.8 Case Illustration A 64-year-old male presented with a chief complaint of sudden vision loss, severe ocular pain, and redness in the right eye (OD) after an accidental hand strike during sleep. The patient was one week postoperative following a Small Incision Cataract Surgery (SICS). Initial examination revealed a visual acuity of light perception (LP), an intraocular pressure (IOP) of 21.9 mmHg, and a Grade IV total hyphema with evidence of fibrin clots. Slit-lamp biomicroscopy confirmed corneal edema and a hazy anterior chamber. Despite three days of intensive conservative management using postural therapy, topical steroids, anti-glaucoma agents, and systemic antifibrinolytics, the visual acuity did not improve. Consequently, a surgical anterior chamber washout was performed. Discussion Total hyphema, often referred to as an